Conference Scene: Advances in breast cancer translational research. (September 2012) - Azim, Hatem A; Andre, Fabrice; Loi, Sherene
IMPAKT is an international annual breast cancer conference that takes place in Brussels, Belgium. The conference mainly focuses on advancements in the field of translational research and the transition of laboratory findings from the bench to the clinic in the field of breast oncology. In 2012, the 4th IMPAKT conference witnessed a variety of exciting data, including new sequencing data of breast cancers, as well as the latest research in the PI3K pathway, which were presented in addition to clinically focused guideline sessions on the use of multigene signatures and molecular classification of breast cancer. There were nearly 700 attendees at the conference this year, which was regarded as a big success.